1996
DOI: 10.1182/blood.v87.10.4358.bloodjournal87104358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of 670 cases in two trials of the European Organization for the Research and Treatment of Cancer Lymphoma Cooperative Group subtyped according to the Revised European-American Classification of Lymphoid Neoplasms: a comparison with the Working Formulation

Abstract: In the Working Formulation (WF), non-Hodgkin's lymphomas (NHL) are grouped according t o their clinical behavior. These disorders are listed as entities defined by morphology, phenotype, and cytogenetics in the proposed Revised European-American Classification of Lymphoid Neoplasms (REAL), the clinical relevance of which is still debated. We analyzed 670 NHL cases included in two randomized clinical trials (EORTC 20855 WF-intermediatelhigh-grade and 20856 WF-low-grade malignancy) with histologic material avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 18 publications
4
23
1
Order By: Relevance
“…Although NU-B1 did not react with recombinant CD79 protein, it reportedly had a pattern of cell surface reactivity identical to that of CD'iSb, when used to stain normal B cells and lymphoid tissues (2). We report here that h'U-Bl recognizes novel human B-cell-restricted molecules, and that previous and present studies support the idea that it could be useful 111 studying the immunophenotyping and classification of leukernidlymphoma and the pathogenesis of mantle cell lym phomas (20)(21)(22).…”
Section: Discussionsupporting
confidence: 83%
“…Although NU-B1 did not react with recombinant CD79 protein, it reportedly had a pattern of cell surface reactivity identical to that of CD'iSb, when used to stain normal B cells and lymphoid tissues (2). We report here that h'U-Bl recognizes novel human B-cell-restricted molecules, and that previous and present studies support the idea that it could be useful 111 studying the immunophenotyping and classification of leukernidlymphoma and the pathogenesis of mantle cell lym phomas (20)(21)(22).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies suggest that the relative incidence of MALT-type lymphomas may vary among different populations [12][13][14][15][16]. In a National Institutes of Health (NIH)-sponsored epidemiologic study of 1,378 non-Hodgkin's lymphomas from eight different geographic areas in four continents using REAL classification, the relative incidences of MALT lymphoma varied from 3% in London to 13% in Lyon, although the differences were not statistically significant [12].…”
Section: Introductionmentioning
confidence: 98%
“…In a National Institutes of Health (NIH)-sponsored epidemiologic study of 1,378 non-Hodgkin's lymphomas from eight different geographic areas in four continents using REAL classification, the relative incidences of MALT lymphoma varied from 3% in London to 13% in Lyon, although the differences were not statistically significant [12]. MALT-type lymphoma is the second most common lymphoma subtype in Korea, comprising 16.7% of all non-Hodgkin's lymphomas [17], a significantly higher rate than the reported rates of 5% and 6% in European population by two large-scale studies [14,16,17]. In cases of gastric MALT lymphoma, a controlled study has shown a higher incidence of gastric MALT lymphoma in northeastern regions of Italy, where H. pylori infection is prevalent, when compared with a region of England with the low prevalence rate of H. pylori [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the relative incidence of ocular adnexal MALT lymphoma (OAML) varies among different populations [3]. The proportion of OAML among primary OALs is higher in Korea (86-98%) than in Western countries (50-78%) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%